“Faith, Hope, and Charity”: The Role of Good Faith in Construction – a Common Law Perspective - Bailey, Julian (2020)
Issues of “good faith” in the performance of construction and engineering contracts are common. Moreover, “good faith” issues arise in most jurisdictions of the world, including common law and civil law jurisdictions. This paper considers the approach taken by English common law to the legal concept of “good faith”. It considers the consequences of English law not embracing “good faith” in commercial law in any general way, including in relation to construction and engineering contracts, and some of the doctrines developed by English law to ameliorate the potentially harsh consequences of a party exercising its contractual rights in an unfair manner. Consideration is also given to the New Engineering Contract and other forms of contract which expressly require parties to act in good faith.